75 ways for managers to hire, develop, and keep great employees - Falcone, Paul (AMACOM, a division of American Management Association, 2016)
Now in this accessible and practical playbook, HR expert and author Paul Falcone shows readers how to: Identify the best and the brightest talent Hire for organizational compatibility Communicate constructively Address uncomfortable workplace situations Create an environment that motivates Retain restless top performers Reengage your team after a layoff or during times of adversity Skillfully conduct performance reviews Take corrective action Sidestep litigation landmines Delegate in a way that develops your staff And much, much more.